2019
DOI: 10.1111/ele.13263
|View full text |Cite
|
Sign up to set email alerts
|

Deeply conserved susceptibility in a multi‐host, multi‐parasite system

Abstract: Variation in susceptibility is ubiquitous in multi-host, multi-parasite assemblages, and can have profound implications for ecology and evolution in these systems. The extent to which susceptibility to parasites is phylogenetically conserved among hosts can be revealed by analysing diverse regional communities. We screened for haemosporidian parasites in 3983 birds representing 40 families and 523 species, spanning~4500 m elevation in the tropical Andes. To quantify the influence of host phylogeny on infection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 99 publications
(111 reference statements)
9
59
3
Order By: Relevance
“…Contrary to previous studies demonstrating an increase of prevalence with increasing elevation across the tropical Andes (Barrow et al, 2019;Galen & Witt, 2014;González et al, 2014;Lotta et al, 2016), we have shown no effect of altitude (Currie & Adler, 2008;McCreadie, Adler, & Hamada, 2005).…”
Section: The Highest Probability Of a Bird Being Infected Withcontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous studies demonstrating an increase of prevalence with increasing elevation across the tropical Andes (Barrow et al, 2019;Galen & Witt, 2014;González et al, 2014;Lotta et al, 2016), we have shown no effect of altitude (Currie & Adler, 2008;McCreadie, Adler, & Hamada, 2005).…”
Section: The Highest Probability Of a Bird Being Infected Withcontrasting
confidence: 99%
“…This allowed for more precise estimation of regression coefficients than using a single consensus tree and was considered more appropriate than running sequential models across different trees. Finally, the β coefficients in Equation (2) (Barrow et al, 2019;Lutz et al, 2015). As sex information was missing for 1,424 birds, we imputed these missing values using…”
Section: Phylogenetic Logistic Regressions To Predict Infection Promentioning
confidence: 99%
“…To better understand the effect of host ecological factors, research needs to account for host phylogenetic relationships in driving susceptibility to infection and subsequent disease transmission. In this study, we demonstrate the importance of host phylogenetic relationships in in uencing variation in infection risk to avian haemosporidians, which is consistent with previous work by Barrow et al (2019). Higher magnitude of phylogenetic signal in the case of Haemoproteus compared to Plasmodium parasites tends to be coherent with their host speci city patterns in our community [32].…”
Section: Discussionsupporting
confidence: 91%
“…Although several factors have been proposed to explain variation in parasite prevalence and infection risk among individuals and host species [13,14,41,47,50,51], it remains unclear whether the role of host ecological traits are generally predictable or whether they are idiosyncratic across hosts, parasites and environmental conditions and context dependent. Additionally, evolutionary history of host species can confound the relationship between ecological traits and parasite infection risk as closely related species are more likely to share risk factors compared to non-related host species [52]. Despite this, surprisingly few studies have taken evolutionary history of the hosts into account and thus, the importance of host evolutionary history in predicting infection risk is less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Both variables were obtained at 10 × 10 km resolution using the MODISTools R package (Tuck et al., 2014) and included as mean values, averaged across months when peak haemosporidian transmission is likely to occur in our study region: May–August. Finally, we included elevation (meters above sea level) as a predictor based on previous evidence that high‐elevation environments show increased prevalence of Leucocytozoon parasites (Barrow et al., 2019; Galen & Witt, 2014). Elevation for each site was extracted from Amazon Web Services (https://registry.opendata.aws/terrain-tiles/) using functions in the elevatr r package (Hollister & Shah, 2017).…”
Section: Methodsmentioning
confidence: 99%